Dampak Karakteristik Pada Profitabilitas Bank Umum Yang Terdaftar Di Bursa Efek Indonesia - Sri Retnoningsih; Ernawati Budi Astuti (LP2M, 2019)
Abstract This study explains the effect of management efficiency and deposits on profitability. The sample of this study was 92 banking industries listed on the Indonesia Stock Exchange in the period of 2016-2019. Indonesia's banking profitability is highest among neighboring countries, so many foreign banks are interested in acquiring national banks. The sampling technique used was purposive sampling. In this study the SPSS method was used. Hypothesis test results show that used to determine the variable management efficiency, deposits to profitability prove the hypothesis proposed is proven true. The R2 test results obtained a value of 0.272. Based on the test results found that the variable management efficiency, Deposits on profitability significantly influence. Keywords: Deposit, Management efficiency, Banking, Profitability.